Evaluate accuracy of EC2 on shear prediction for RC beams - Chen, Nengjian (Nanyang Technological University, 2019)
The rise of high-rise buildings and long-span bridges has resulted in a higher demand of high strength materials over the past few decades. However, Eurocode 2 impose a limit on concrete compressive strength of 90 MPa and steel yield strength of 600 MPa in shear design, this restriction prevents designers from fully utilize high strength of concrete and steel in shear design, which results in the unconservative prediction of ultimate shear capacities for RC beams. Therefore, this report aims to evaluate the impact of various high strength materials on the accuracy of EC2 in predicting ultimate shear capacity of RC beams. The evaluation will be done through statistical analysis of various databases composed of all previous experimental testing of RC beams with and without stirrups, and results from an experimental investigation aimed at addressing deficiencies in the compiled databases. Meanwhile, to find paucity within previous research of experimental shear testing on RC beams, which will be recommended for future studies. The research has revealed that the EC2 produced an unconservative shear prediction with adopting high-strength material in design and construction of RC beams. This observation was reinforced through the various analysis of databases. Possible solutions were proposed for beams with and without stirrups to tackle the problems discovered in this report. Furthermore, this report recommended to use with beam categories of H(C)-N(L)-H(S), H(C)-H(L)-N(S) , H(C)-N(L)-N(S), N(C)-H(L)-N(S) , as full strength of steel and concrete can be applied in design without compromising safety. Lastly, a few recommendations were provided for future studies at the end of report. Note: H(C), H(L) and H(S) = High-strength concrete, longitudinal and shear reinforcement, respectively. N(C), N(L) and N(S) = Normal-strength concrete, longitudinal and shear reinforcement, respectively.